High‐performance HTL‐free perovskite solar cell: An efficient composition of ZnO NRs, RGO, and CuInS2 QDs, as electron‐transporting layer matrix. (21st June 2020) - Taheri‐Ledari, Reza; Valadi, Kobra; Maleki, Ali
Abstract: A hole‐transporting layer (HTL)‐free perovskite solar cell (PSC) with fluorine‐doped tin oxide (FTO)/nanocomposite electron‐transporting layer (ETL)/perovskite/Au structure is presented that takes advantage of a novel ternary nanocomposite constructed of zinc oxide (ZnO) nanorods, reduced graphene oxide (RGO), and copper indium sulfide quantum dots (CuInS2 QDs), as ETL. Concisely, the photoelectric and photovoltaic properties of all the individual, binary, and ternary composites were monitored by using of the photoluminescence (PL) spectroscopy, UV‐visible (vis) spectroscopy, J‐V curves, and incident photon‐to‐current conversion efficiency (IPCE) spectra studies. The comparative values exhibited a noticeable benefit for the ZnO‐RGO5%‐CuInS2 20% ternary nanocomposite as an appropriate ETL for PCS. Also, the comparative structural studies on the individual nanoscale components, binary, and ternary nanocomposite (with different percentages of CuInS2 QDs) were precisely performed by Fourier transform infrared (FT‐IR), energy‐dispersive X‐ray (EDX), X‐ray diffraction (XRD), Raman spectroscopy, and field emission scanning electron microscopy (FESEM), as well. Overall, after careful optimization of the ETL, a15.74% efficiency was resulted through applying the prepared ZnO‐RGO5%‐CuInS2 20% composite in a HTL‐free PCS with 0.33 cm 2 active area. Abstract : A novel ternary ZnO nanorods, reduced graphene oxide, and CuInS2 quantum dot nanocomposite as an electron‐transporting layer (ETL) are prepared for enhancing the efficiency of the perovskite solar cells (PSCs). The photovoltaic and photoelectric properties of the cell are substantially enhanced through using these materials as ETL due to including the band gaps close to each other, which results in reduced electron recombination and great efficiency (15.76%) in less expensive hole‐transporting layer (HTL)‐free PSCs.